Inhibitory effects of Sargassum polycystum on tyrosinase activity and melanin formation in B16F10 murine melanoma cells - Chan, Y.Y.; Kim, K.H.; Cheah, S.H. (Elsevier, 2011)
ETHNOPHARMACOLOGICAL RELEVANCE: Sargassum polycystum, a type of brown seaweed, has been used for the treatment of skin-related disorders in traditional medicine.